Differences in Adolescent E-cigarette and Cigarette Prevalence in Two Policy Environments: South Korea and the United States. Issue 8 (5th September 2017) - Cho, Hong-Jun; Dutra, Lauren M; Glantz, Stanton A
Abstract: Introduction: In the context of different regulatory environments, different patterns of e-cigarette use have emerged among adolescents worldwide. The United States and South Korea are two examples, the latter of which has maintained much more extensive regulation of e-cigarettes. Methods: This analysis compares the prevalence of e-cigarette and conventional cigarette use between 2011 and 2015 from the Korean Youth Risk Behavior Web-based Survey and the U.S. National Youth Tobacco Survey, both nationally representative samples of middle and high school students that use similar questions. Results: E-cigarette prevalence (past 30 days) among South Korean adolescents decreased from 4.7% in 2011 (95% confidence interval [CI]: 4.4–5.0) to 4.0% (3.7–4.3) in 2015 but increased dramatically among US adolescents from 0.9% (0.7–1.2) to 11.2% (9.9–12.7). Cigarette prevalence (past 30 days) decreased in South Korea from 12.1% (11.6–12.7) to 7.8% (CI: 7.3–8.3) and in the United States from 11.1% (9.5–12.6) to 6.1% (5.1–7.3). Combined prevalence of cigarette and e-cigarette use (adjusting for dual users) decreased in South Korea from 13.2% (12.7–13.8) to 8.5% (8.0–9.1) but increased in the United States from 11.3% (9.7–12.9) to 14.0% (12.4–15.7). Conclusions: In South Korea, where e-cigarettes are extensively regulated, adolescent e-cigarette use remained stable at a low level, whereas in the United States, where e-cigarette regulation has been limited, e-cigarette use increased. Combined e-cigarette plus cigarette use declined in South Korea whereas it increased in the United States. The restrictive policies in South Korea likely contributed to lower overall product use. Implications: This paper compared the strength of regulation of South Korea and the United States with the prevalence of adolescents' e-cigarette and cigarette use and suggests that more restrictive policies likely to contribute to lower e-cigarette use and overall use of e-cigarette and cigarette.